Remote work as a carbon emission reduction strategy: South Africa - du Toit, Peter (Henry Stewart Talks, 2021)
This case study looks at a region of South Africa as an example of the difference that remote work/work from home could make in CO2 emissions, and touches on the strategies necessary to make this change a long-term one.